Racial Disparities and the Effect of County Level Income on the Incidence and Survival of Young Men with Anal Cancer - Markian M. Bojko; Robert J. Kucejko; Juan L. Poggio (Mary Ann Liebert, 2018)
Purpose: Prior studies have identified a racial disparity in incidence and survival of squamous cell carcinoma of the anus (SCCA) in the young African American male population. We aim to determine whether racial disparities are independent of income and urban location. Methods: The National Cancer Institute's Surveillance of Epidemiology and End Results database was queried for data on patients with SCCA for the years of 2000?2013. Cox regression was used to determine the effect of race, county median family income, rural?urban continuum, and stage of disease on overall survival. Results: The incidence rate of SCCA was significantly higher in black men <50 years old than in white men. Black race had a hazard ratio of 1.55 (confidence interval [CI] 1.33?1.81) when controlling for age, stage, income, and urban?rural status. Each $10,000 increase in county median family income was protective with a hazard ratio of 0.90 (CI 0.86?0.94). Residence in a metropolitan area did not significantly affect survival. Conclusions: The lower survival of black men <50 years old with SCCA is independent of income, urban location, and stage of disease. Further efforts are needed to target this at-risk population and the authors suggest wide application of previously validated screening programs for anal dysplasia.